2013
DOI: 10.1093/humupd/dmt010
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis: hormone regulation and clinical consequences of chemotaxis and apoptosis

Abstract: Estrogens and progestogens modulate chemotaxis and apoptosis in human endometrium and endometriotic cells and tissues. These endocrine and paracrine pathways are perturbed in women with endometriosis, contributing to inflammatory responses, abnormal tissue remodeling, therapeutic refractoriness and disease persistence. Ultimately, they promote adhesion formation and the clinical symptoms of pelvic pain and infertility. A more detailed understanding of the molecular mechanisms involved will offer new opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
172
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(197 citation statements)
references
References 133 publications
(152 reference statements)
3
172
0
11
Order By: Relevance
“…8 Endometriosis has multifactorial causes, including retrograde menstruation, genetic and environmental factors, alteration of the immune system, and ectopic differentiation of mesenchymal stem cells. 9,10 Estrogen plays a necessary role in the pathophysiology of endometriosis, 11 since it promotes the implantation of endometrial tissue in the peritoneum, has proliferative and antiapoptotic effects in endometrial cells, and stimulates local and systemic inflammation. 12,13 On the basis of the "estrogen threshold hypothesis," complete estrogen suppression may not be needed to control endometriosis-associated pain, and estrogen may be adjusted to a level that is adequate to control pain but minimizes hypoestrogenic effects.…”
mentioning
confidence: 99%
“…8 Endometriosis has multifactorial causes, including retrograde menstruation, genetic and environmental factors, alteration of the immune system, and ectopic differentiation of mesenchymal stem cells. 9,10 Estrogen plays a necessary role in the pathophysiology of endometriosis, 11 since it promotes the implantation of endometrial tissue in the peritoneum, has proliferative and antiapoptotic effects in endometrial cells, and stimulates local and systemic inflammation. 12,13 On the basis of the "estrogen threshold hypothesis," complete estrogen suppression may not be needed to control endometriosis-associated pain, and estrogen may be adjusted to a level that is adequate to control pain but minimizes hypoestrogenic effects.…”
mentioning
confidence: 99%
“…Altered E 2 and P receptor activity and impaired local growth factor and cytokine expression induce proliferation of endometrial cells, peritoneal adhesion, and inflammation of endometriotic lesions (3). Among growth factors, an involvement of transforming growth factor b (TGF-b) superfamily in cell proliferation, immune function, and apoptosis in endometriosis has been shown (4)(5)(6). Antim€ ullerian hormone (AMH), also known as m€ ullerian inhibiting substance (MIS), is a member of TGF-b superfamily (7), playing an essential role in sexual differentiation.…”
mentioning
confidence: 99%
“…Therefore, considering that COX-2 overexpression is a frequent finding in ectopic endometrium tissue [29][30][31] , we may assume that the direct injection of aspirin to endometriosis foci may stimulate apoptosis and destroy endometriotic cells (as observed in our experimental study) through a mechanism involving inhibition of COX proteins.…”
Section: Gross and Histological Measurementsmentioning
confidence: 67%
“…This particular result clearly demonstrates the maintenance and Another issue to consider is that it has been well demonstrated that there is an apoptotic dysregulation in the pathophysiology of endometriosis, although it is unlikely that apoptosis per se will explain the whole pathophysiology of endometriosis [29][30][31] . Thus, as it has been demonstrated that increased cell proliferation and decreased endometrial cell survival and apoptosis facilitate ectopic implantation of endometriotic cells in women with endometriosis [29][30][31] .…”
Section: Gross and Histological Measurementsmentioning
confidence: 91%
See 1 more Smart Citation